2019
DOI: 10.1177/0145561319874017
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Fasciitis of the Neck

Abstract: A 67-year-old woman with a history of type 2 diabetes was referred to our hospital and reported painful swelling on the left neck over a 2-week period. She had visited another hospital where she was administered oral antibiotics, but her symptoms deteriorated. Her temperature, pulse, and blood pressure were 35.3 C, 107 bpm, and 92/50 mm Hg, respectively. During physical examination, bruising, tenderness, and severe swelling of the left neck were noted (Figure 1A). Laboratory data revealed the following: a whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In most cases, multiple episodes of debridement are necessary, potentially resulting in significant soft tissue defects. After all nonviable tissue is excised and the infection is cleared, reconstruction with soft tissue flaps may be necessary, especially in patients with massive defects [ 15 , 16 ]. The patients were managed with IV polyantibiotic therapy, analgesics, IV fluids, wound debridement and extraction of the offending teeth.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, multiple episodes of debridement are necessary, potentially resulting in significant soft tissue defects. After all nonviable tissue is excised and the infection is cleared, reconstruction with soft tissue flaps may be necessary, especially in patients with massive defects [ 15 , 16 ]. The patients were managed with IV polyantibiotic therapy, analgesics, IV fluids, wound debridement and extraction of the offending teeth.…”
Section: Discussionmentioning
confidence: 99%
“…CNF presents as a rapid extensive infection with cervical erythema, tenderness, crepitus, respiratory distress, and sepsis [ 11 ]. Previous studies have shown that some patients may present with concurrent DNI and CNF [ 12 , 13 ]. Therapeutic management in patients with the coexistence of these two lethal diseases is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment for deep neck infection mainly consists of antibiotic administration and surgical drainage with postoperative wound irrigation [ 3 ]. Postoperative irrigation should be performed every 4–8 hours by doctors according to disease severity, which imposes additional physical and time-related burdens on medical staff [ [4] , [5] , [6] ]. Herein, we present a case in which an innovative continuous-irrigation approach was applied for wound care following surgery for deep neck infection.…”
Section: Introductionmentioning
confidence: 99%